A general geomorphological recession flow model for river basins. Issue 8 (7th August 2013) - Biswal, Basudev; Nagesh Kumar, D.
<x xml:space="preserve">Abstract</x> [1] Recession flows in a basin are controlled by the temporal evolution of its active drainage network (ADN). The geomorphological recession flow model (GRFM) assumes that both the rate of flow generation per unit ADN length (q) and the speed at which ADN heads move downstream (c) remain constant during a recession event. Thereby, it connects the power law exponent of –dQ/dt versus Q (discharge at the outlet at time t) curve, α, with the structure of the drainage network, a fixed entity. In this study, we first reformulate the GRFM for Horton‐Strahler networks and show that the geomorphic α (αg) is equal to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3j1qqdrd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />D/(D−1)</alternatives>, where D is the fractal dimension of the drainage network. We then propose a more general recession flow model by expressing both q and c as functions of Horton‐Strahler stream order. We show that it is possible to have α =α g for a recession event even when q and c do not remain constant. The modified GRFM suggests that α is controlled by the spatial distribution of subsurface storage within the basin. By analyzing streamflow data from 39 U.S. Geological Survey basins, we show that α is having a power law relationship with recession curve peak, which indicates that the spatial distribution of subsurface storage varies across recession events.